A Educação Ambiental como Início, Meio e Fim das Atividades Universitárias do Departamento de Ciências da FFP/UERJ. - Douglas de Souza Pimentel; Maria Cristina Ferreira dos Santos; Ana Angélica Monteiro de Barros (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
The activities developed at the three University main themes, Graduation-Research-Extension related to Environmental Education in Rio de Janeiro by the Department of Sciences of Faculty for Teachers´ Formation (FFP) of the State University of Rio de Janeiro (UERJ) include: (i) environmental recovery of degraded area around FFP campus in São Gonçalo; (ii) integrated teaching of Ecology, Botany and Zoology and activities of extension in the Desengano State Park in Santa Maria Madalena; (iii) research projects in the Serra da Tiririca State Park in Niterói. This paper focus on how these activites that initiated from different perspectives are based on Environmental Education as an unifying and enriching line of action of professors, students and local communities.